2006
DOI: 10.1007/s11064-006-9048-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Protection against Dopamine Loss Induced by Intracerebroventricular Administration of 6-Hydroxydopamine

Abstract: Calcitriol has been implicated as an agent that has neuroprotective effects in various animal models of diseases, possibly by upregulating glial cell line-derived neurotrophic factor (GDNF). The present study examined the neuroprotective effects of calcitriol in a model of early Parkinson's disease. Rats were treated daily with calcitriol or saline for 7 days before an intraventricular injection of 6-hydroxydopamine (6-OHDA), and then for 1 day or daily for 3(1/2) to 4 weeks after lesioning. Evoked overflow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 45 publications
2
87
0
3
Order By: Relevance
“…Regarding, for example, the effects of vitamin D on nerve growth factor synthesis or neurotransmitter like serotonin, lower levels may contribute to depression (Brown et al, 2003;Cass et al, 2006;Garcion et al, 2002;Smith et al, 2006;Wion et al, 1991). On the other hand, vitamin D deficiency may also be a consequence of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding, for example, the effects of vitamin D on nerve growth factor synthesis or neurotransmitter like serotonin, lower levels may contribute to depression (Brown et al, 2003;Cass et al, 2006;Garcion et al, 2002;Smith et al, 2006;Wion et al, 1991). On the other hand, vitamin D deficiency may also be a consequence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of vitamin D receptors and vitamin D-activating enzymes in several parts of the human brain known to contribute to the regulation of mood like the hippocampus, hypothalamus and prefrontal cortex provide plausible biological explanations for the relationship between vitamin D deficiency and low mood (Eyles et al, 2005). In addition, there is evidence that vitamin D is a potent inducer of nerve growth factor synthesis (Brown et al, 2003;Wion et al, 1991) and is involved in the expression of monoamines, such as norepinephrine and serotonin, which are associated with depression Garcion et al, 2002;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been linked to key neurotrophic agents, such as nerve growth factor and glial cell-derived neurotrophic factor [3,4], and animal experiments have suggested that the active form of the vitamin has 'neuroprotective' features. For example, pre-treatment with vitamin D attenuates the effects of various stressors, including 6-hydroxydopamine-induced neurotoxicity [5,6]. Moreover, vitamin D deficiency in adult rats has been shown to exacerbate stroke injuries and lead to more severe post-stroke behavioural impairments and this was accompanied by lower levels of the neuroprotective hormone, insulin-like growth factor 1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Links between dopamine and vitamin D have also been identified in adult animals. Vitamin D has been shown to promote the synthesis of tyrosine hydroxylase, the rate-limiting enzyme of dopamine synthesis and also to increase basal levels of dopamine within the central nervous system after localised injection of vitamin D 3 [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that dietary regulation of vitamin D may be effective in protecting individuals from PD or slowing PD progression. In animal and cell culture models of PD, vitamin D supplementation was found to be beneficial in slowing disease progression (Wang et al, 2001;Smith et al, 2006;Holick, 2007). In human studies, however, high consumption of food containing vitamin D increased the risk of PD Vitamin C or ascorbate is highly concentrated in the central nervous system and its neuroprotective capabilities show promise in reducing lipid peroxidation levels and increasing catalase activity (Santos et al, 2008).…”
Section: Vitamin D C and Ementioning
confidence: 99%